Task-based material design in Japanese tour guide courses: fostering adaptability and sustainable learning - Liu, Qiannan; Eng Wong, Bee; Peter Bailey, Richard (Institute of Advanced Engineering and Science, 2025)
The rapid growth of international tourism has significantly increased the number of Chinese visitors to Japan and vice versa, leading to a heightened demand for tour guides fluent in Japanese. However, the lack of specialized Japanese tour guide courses in Chinese undergraduate tourism programs has resulted in a shortage of qualified professionals. Therefore, developing teaching materials that support the learning of Japanese among Chinese students aiming to become fluent tour guides is essential to fill this gap. This study aims to develop and evaluate task-based teaching materials designed to enhance trainees’ oral communication skills and professional adaptability for the Japanese tour guide purpose (JTGP) in real-world guiding scenarios. The task-based material design approach proposed in this research focuses on improving students’ Japanese oral tour guide abilities while fostering adaptability and sustainability in their learning. The study was conducted with tourism students from Ningxia University Xinhua College, utilizing tests, semi-structured interviews, and observational data. Action research was employed to optimize the Japanese task-based materials, ensuring that they effectively promote language development while also targeting the cultivation of adaptability and sustainability of learning. The results indicate a strong student interest in the task-based courses, particularly the interactive elements, which have significantly enhanced their adaptability to the tour guide role and capacity for sustainable development thinking.